Recovery Agents’ Group Communication Dynamics in Supporting Resilience through Community-Based Intervention - Esdras Idi Alfero Ginting; Dewi Kurniawati; Maulana Andinata Dalimunthe (Ali Institute of Research and Publication, 2026)
This study examines the dynamics of group communication among recovery agents in building the resilience of former drug addicts in Sekip Village, Lubuk Pakam District, Deli Serdang Regency, North Sumatra. The study is grounded in the local vulnerability of Sekip Village to drug abuse and illicit drug circulation, as indicated by its classification as a high-risk area in the 2021 Drug-Prone Area Map issued by the National Narcotics Agency of Indonesia. In this context, community-based recovery efforts are important because access to formal rehabilitation services remains uneven, particularly for socially and economically vulnerable groups. This study employed a qualitative approach using in-depth interviews, observation, documentation, and source triangulation. The findings show that recovery agents play roles as facilitators, mentors, communicators, and connectors between former drug addicts and available social resources. Group communication dynamics create a safe psychological climate, strengthen social support, encourage openness, and support adaptive coping mechanisms. Supporting factors include community involvement, village government support, coordination among recovery agents, and guidance from authorized institutions. Meanwhile, inhibiting factors include social stigma, limited facilities, limited funding, and internal differences of opinion. The study concludes that group communication among recovery agents contributes to the resilience-building process by helping former drug addicts maintain recovery motivation, prevent relapse, and reintegrate into society.